PERNIKAHAN MELALUI TELEPON DAN REFORMASI HUKUM ISLAM DI INDONESA - Asnawi, Habib Shulton (UIN Sunan Kalijaga Yogyakarta, 2012)
Islamic law is universal. The law must be developed in accordance with socialneeds, as well as the fiqh rule that